2003
DOI: 10.1002/hbm.10139
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain activity in response to a visual stimulus

Abstract: Previous studies have demonstrated the use of functional magnetic resonance imaging (fMRI) to assess fetal brain activity. To extend these studies, a fetal fMRI experiment using a visual stimulus has been performed at 0.5 T. This used a block fMRI paradigm with a bright, constant-intensity light source being shone at the maternal abdomen for 8 sec followed by 16 sec of darkness. This was repeated typically 40 times on nine subjects all of whom were greater than 36 weeks gestational age. Of these, one could not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 28 publications
1
49
0
1
Order By: Relevance
“…Using a visual stimulus provided by a red LED cluster on the maternal abdomen, five of eight fetuses showed some activation, in four of these, the area was found within the frontal region. There was no significant activation detected within the visual areas (Fulford et al, 2003).…”
Section: Functional Imagingmentioning
confidence: 66%
“…Using a visual stimulus provided by a red LED cluster on the maternal abdomen, five of eight fetuses showed some activation, in four of these, the area was found within the frontal region. There was no significant activation detected within the visual areas (Fulford et al, 2003).…”
Section: Functional Imagingmentioning
confidence: 66%
“…These studies, however, (Eswaran et al, 2002bMcCubbin et al, 2007;Sheridan et al, 2008;Matuz et al, 2012;Fulford et al, 2003) use similar methodologies in some aspects of their design, such as stimulus duration. It is likely that critical aspects of design, such as the brightness of the light source, area of illumination and the number of presentations to the foetus do have an impact on the response rates and latencies that have been found.…”
Section: Visual Processing: Summarymentioning
confidence: 97%
“…One study using fMRI has investigated the effect of light on foetal response, which could potentially explain which of these factors, namely brightness, wavelength, or paradigm, caused a difference in response rate (Fulford et al, 2003). Investigating simple responses to light, the authors found a 62% response rate was localised to the frontal cortex in foetuses of at least 36 weeks GA.…”
Section: Visual Processing-fmrimentioning
confidence: 98%
“…La variation d'oxyhé moglobine sera dé tecté e et mesuré e en donnant un signal diffé rent (Bold Oxygenation Level Dependent [BOLD]) [37,38]. Une telle IRM pourrait permettre de localiser la fonction dans le cerveau foetal, mais ceci reste encore trè s confidentiel.…”
Section: Irm Fonctionnelleunclassified